AP-1 signaling pathway promotes pro-IL-1β transcription to facilitate NLRP3 inflammasome activation upon influenza A virus infection. Issue 1 (31st December 2022) - Wan, Pin; Zhang, Simeng; Ruan, Zhihui; Liu, Xueli; Yang, Ge; Jia, Yaling; Li, Yongkui; Pan, Pan; Wang, Wenbiao; Li, Geng; Chen, Xulin; Liu, Zhixin; et al.
ABSTRACT: NLRP3 inflammasome mainly controls interleukin-1β (IL-1β) secretion, leading to cell death called pyroptosis constituting a major antiviral host defense and inflammatory diseases upon viral infection. The RAF-MEK1/2-ERK1/2 cascade and downstream c-Jun/Fos and Activator protein-1 (AP1) signaling pathway control the degree of inflammatory response. Influenza A virus (IAV) infection is known to stimulate NLRP3 inflammasome activation and inflammatory responses. Nevertheless, the detailed mechanism by which IAV induces NLRP3 inflammasome activation involved in transcription of pro-IL-1β mRNA remains elusive. In our study, we found that IAV infection promotes pro-IL-1β mRNA transcription and activates NLRP3 inflammasome. Detailed studies reveal that type I interferon (IFN-α/IFN-β) as well as U0126 (a selective inhibitor of MEK-1 and MEK-2) typically inhibit IAV-mediated NLRP3 inflammasome activation via downregulating pro-IL-1β mRNA. Moreover, knock-down of c-Jun decreases pro-IL-1β mRNA and inhibits NLRP3 inflammasome activation upon IAV infection. Overall, the findings uncover that AP-1 signaling pathway promotes NLRP3 inflammasome activation upon IAV infection, which provides a new idea for the therapy of NLRP3 inflammasome-associated inflammatory diseases.